Notes on the Wild Tomistoma Populations in Western Sarawak, Malaysian Borneo - Ruhana, Hassan; Rambli, Ahmad; Muhammad Amirul Arib, Md Adzhar; Mohd Izwan Zulaini, Abdul Gani; Anuar, Ayob; Ramlah, Zainudin (Hindawi Publishing Corporation, 2016)
Tomistoma schlegelii, the Freshwater Malayan Gharial or Tomistoma (local name: buaya jejulong), is secretive in nature; thus, very limited information is currently available on its wild population, especially in Sarawak. The objective of this study is to describe effort in assessing the Tomistoma wild populations in Ulu Sebuyau, Samarahan, and Serian, western Sarawak. Despite many challenges faced, this research has been successful at different levels. There was no Tomistoma seen during day surveys (2014-2015) in tributary of Samarahan River (Samarahan), Bunga-Baki River (Serian), and Kepayang River (Ulu Sebuyau). However, the research team came across two incidents of Tomistoma captured by the local people: (i) an adult male Tomistoma, captured in February 2015 in peat swamp area of Samarahan River tributary, and (ii) a hatchling, caught in Bunga-Baki River in March 2015. The sightings of Tomistoma in Kepayang River were reported by local people in February 2016; however, no individual was captured. The presence of hatchling in Bunga-Baki River indicates that a breeding population is most likely to occur in the area, and this gives hope for future conservation of Tomistoma in Sarawak. All sampling sites recorded almost similar water quality parameters and landscape of peat swamp areas, which previous studies claimed to be the potential Tomistoma habitats. The findings of this study should help relevant state agencies to step up efforts related to conservation of Tomistoma in Sarawak.